BIO302: Basic Techniques in Biology - UiTM, Faculty of Applied Sciences (2023)
This course emphasizes laboratory techniques commonly applied in biological studies, including techniques in microbiology, histology, DNA technology, biochemical analysis, and field investigation. The course covers the underlying theory behind the application of these techniques and the associated technology and instruments.